Model of Sustainable Belawan Harbor Waters Pollution Management Scheme - Tarigan, Simon; Rauf, Abdul; ., Rahmawaty; Harahap, R. Hamdani (Journal of Ecohumanism, 2024)
This study aims to analyze the impact of industrial activities on water quality in Belawan Port, Medan City. The methods used included field surveys, water sampling, and in-depth interviews with stakeholders and communities around the harbor. The results showed that industrial activities at the port significantly affected water quality parameters such as acidity, heavy metal concentration, and the number of pathogenic microorganisms. In addition, the socio-economic conditions of the community around Belawan Port also affect awareness of the environment and the cleanliness of the waters. This study concludes that water pollution management in Belawan Harbor requires an integrated approach between the government, port management, industry, and local communities. Collaborative efforts are needed to implement more effective and sustainable policies to maintain environmental sustainability in this port area. Key recommendations include the establishment of an Integrated Water Quality Management Team and increased active participation from all stakeholders in keeping the waters and environment around Belawan Port clean.